Consensus clinical recommendations for the management of plasma lipid disorders in the Middle East: 2021 update. (February 2022) - Alsayed, Nasreen; Almahmeed, Wael; Alnouri, Fahad; Al-Waili, Khalid; Sabbour, Hani; Sulaiman, Kadhim; Zubaid, Mohammad; Ray, Kausik K.; Al-Rasadi, Khalid
Abstract: Background and aims: Disorders of plasma lipids remain key risk factors for the development of atherosclerotic cardiovascular disease (ASCVD) in the Middle East and are estimated to increase more dramatically in the next decade than in any other global region except Africa. This statement is an update to the 2016 consensus clinical recommendations for the management of plasma lipid disorders in the Middle East, following the evaluation of newer cholesterol-lowering agents in randomised controlled cardiovascular outcome trials, as well as the publication of revised international guidelines. Methods: A multidisciplinary panel of regional experts was convened to update the consensus clinical recommendations for the management of plasma lipids in the Middle East. The recommendations constructed in 2016 were reviewed against emerging research since publication. Results: Newly developed Middle East ASCVD risk categories were established using the multiple risk group categories from the recently updated international guidelines and the epidemiological evidence from the Gulf Region. These consensus recommendations support a more intensive reduction of LDL-C across cardiovascular risk categories. Alongside low-density lipoprotein cholesterol, we recommend non-high-density lipoprotein cholesterol as a primary treatment target. Lifestyle modifications remain the first-line treatment recommendation for all patients. The first-line pharmacological treatment in patients with dyslipidaemia is statin therapy, with a number of second-line agents available. The selection of a second lipid-lowering agent for combination therapy with statin should be based on the lipid-lowering target of the patient. Guidance is also provided on the management of underlying conditions and special populations; of particular pertinence in the region are familial hypercholesterolaemia, diabetes and metabolic dyslipidaemia. New therapies have emerged from research that found positive outcomes in reducing low-density lipoprotein cholesterol levels. The initial results of these newly researched drugs strongly indicate their inclusion as future therapies in dyslipidaemia management in the Middle East. Conclusions: These updated consensus clinical recommendations provide practicing clinicians with comprehensive, region-specific guidance to improve the detection and management of plasma lipid disorders in patients in the Middle East. Graphical abstract: Image 1 Highlights: Plasma lipid disorders are of increasing prevalence and concern in the Middle East. Updated regional clinical recommendations consider recent international guidelines. Middle East-specific cardiovascular risk categories were developed. Recommendations support a more intensive treatment across risk categories. Guidance considers screening, risk levels, treatment, and special populations.